Multiple Intelligences in Digital Physics Learning for Education for Sustainable Development - Hanan Zaki Alhusni; Titin Sunarti; Hanandita Veda Saphira; Riski Ramadani (Journal of Current Studies in SDGs, 2025)
Objective: This study aims to synthesise research on the application of Multiple Intelligences (MI) in digital physics learning within the framework of Education for Sustainable Development (ESD). The goal is to map trends, highlight opportunities for personalised, sustainability-oriented learning, and identify gaps that hinder the integration of MI and digital technologies to foster sustainability competencies. Method: A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Articles were collected from Google Scholar, Scopus, IEEE Xplore, ERIC, and ScienceDirect, limited to peer-reviewed studies published between 2018 and 2023 in English or Indonesian. Forty eligible studies were analysed thematically and through content analysis. Results: The findings show that MI-based digital learning enhances students' motivation, engagement, conceptual understanding, and academic performance. Interactive simulations, video-based modules, virtual experiments, and AR/VR applications offer personalised learning aligned with students' dominant intelligences. MI also supports ESD competencies such as critical thinking, collaboration, and sustainability awareness, though aspects like environmental literacy, social responsibility, and ethical reasoning remain underexplored. Novelty: This review uniquely links the MI, physics education, and ESD domains, which are rarely integrated in prior studies. It emphasises MI's potential to enhance cognitive outcomes while embedding sustainability values into physics education. A conceptual roadmap is proposed to align MI-based digital physics learning with the Sustainable Development Goals.